Ancient South Arabian Legal Texts with Semitic Parallels and Their Anthropological Background - Daum, Werner (JAOS, 2024)
This review article deals with legal texts prominently inscribed on a city gate of Timnaʿ, the capital of the Ancient South Arabian state of Qataban. Following a sketch of the history of the region and its languages, the reviewer considers the legal texts published in the reviewed volume dealing with homicide, the attribution of tithes, infanticide, and other matters. It is pointed out that their interpretation by the author would have benefited from comparisons with Yemeni anthropological data that have not changed since pre-Islamic times.